Interpreting-Related Technology as an Assistant in the Classroom and as a Self-Directed Lifelong Learning Method - Mira-Rueda, Concepción (My University, 2023)
Very little research has been conducted on interpreting-related tech- nology. The reasons for this may range from the fact that the technology is very new, to the ways in which we can apply it in interpreting. This paper offers two main ways we can apply this technology: as an assistant in the classroom and as a self-directed lifelong learning method for students/interpreters.
Keywords: Traducción - Innovaciones tecnológicas; Interpreting; Technology; Learning; Lifelong; Interpreting-related technology